2022
DOI: 10.3389/fpsyg.2022.1001867
|View full text |Cite
|
Sign up to set email alerts
|

The significance of green entrepreneurial self-efficacy: Mediating and moderating role of green innovation and green knowledge sharing culture

Abstract: Green entrepreneurial self-efficacy (ESE) refers to individuals’ conviction that they can contribute to solving environmental issues and shows self-assurance in their efforts to protect the environment. The present investigation attempts to determine the role of employees’ green ESE in the green innovation (GI) of SMEs. It is also proposed that GI positively impacts organizational environmental, economic, and social performance. This study also evaluates the mediating role of GI and moderating role of the gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 79 publications
4
23
1
1
Order By: Relevance
“…All of these factors can help to strengthen an organisation's relationship between motivation and innovation (Wang and Noe, 2010;Hung et al, 2011;Aljanabi and Kumar, 2012;Peng, 2013;Arfi et al, 2018). However, this study is not in line with one piece of previous research (Guo, 2022), which reported the nonexistence of a moderation effect of KS on GI entrepreneurial self-efficacy.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…All of these factors can help to strengthen an organisation's relationship between motivation and innovation (Wang and Noe, 2010;Hung et al, 2011;Aljanabi and Kumar, 2012;Peng, 2013;Arfi et al, 2018). However, this study is not in line with one piece of previous research (Guo, 2022), which reported the nonexistence of a moderation effect of KS on GI entrepreneurial self-efficacy.…”
Section: Discussioncontrasting
confidence: 62%
“…GI can be developed in businesses by identifying the key factors that contribute to its growth. Various factors, such as personal characteristics, have been identified as being responsible for the development of GI, but no definitive mechanism has been identified (Prodanova et al, 2021;Guo, 2022). GEM is thought to act as a precursor for developing green behaviour in individuals, ultimately benefiting the environment and its surroundings.…”
Section: Mediation Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…GESE has a positive impact on green innovation. Moreover, the study's findings do not confirm the moderating effect of the green knowledge-sharing culture in developing the connection between GESE and green innovation in SMEs (Guo, 2022). Through GESE, country support for entrepreneurship and institutional support for developing entrepreneurship both make a positive and significant impact on green EI (Robayo-Acuña et al, 2023).…”
Section: Green Entrepreneurial Self-efficacy (Gese) As a Mediatormentioning
confidence: 62%
“…2.6 Green entrepreneurial self-efficacy (GESE) GESE refers to people's confidence that they can help to solve environmental problems and can demonstrate self-assurance in environmental protection activities. More specifically, GESE provides firms with a roadmap on how their employees' GESE may assist them in performing better in terms of the environment, economics and society (Guo, 2022). Entrepreneurial self-efficacy (ESE) partially mediates the link between lack of premeditation and lack of perseverance and intentions to become an entrepreneur (Tran et al, 2023).…”
Section: Availability Of Capital (Aoc)mentioning
confidence: 99%